Observações sobre a doutrina do homem-medida : uma tentativa de reconstituição do pensamento de protágoras - Santos, Danilo Pereira dos (2017)
The goal of this research was to analyze the philosophical meaning of the sentence of the fifth century sophist a.C. Protagoras de Abdera: ?Man is the measure of all things: of the things that are, that they are, of the things that are not, that they are not?. That phrasing wording was criticized by philosophers of the time, especially Plato. Drawing from vari-ous sources, I intend to retrace Protagoras' ideas and its philosophical force. I intend to investigate how, in a way, Protagoras contributes to Plato's philosophical reflection and to investigate, on the other hand, whether there are relevant arguments to show that the interpretation of Protagoras's sentence is different from that of Plato .